2007
DOI: 10.1016/j.hrthm.2007.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between arrhythmogenesis and disease activity in cardiac sarcoidosis

Abstract: In cardiac sarcoidosis patients, CAVB develops mainly during the active phase of the disease. Early treatment with corticosteroids might improve AV conduction disturbance. However, sustained VT is not closely linked with disease activity and frequently develops in the advanced stage of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 21 publications
10
108
2
1
Order By: Relevance
“…Small‐sized retrospective studies showed that steroid improved nearly 50% of cardiac sarcoidosis patients with complete AV block 2, 3. Chapelon‐Abric et al demonstrated that clinical response to prednisolone was limited to the early stage of cardiac sarcoidosis 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small‐sized retrospective studies showed that steroid improved nearly 50% of cardiac sarcoidosis patients with complete AV block 2, 3. Chapelon‐Abric et al demonstrated that clinical response to prednisolone was limited to the early stage of cardiac sarcoidosis 6.…”
Section: Discussionmentioning
confidence: 99%
“…It is presumed that the substrate for arrhythmias includes inflammation and following fibrosis because of sarcoidosis as well as acute fulminant myocarditis. Complete AV block because of cardiac sarcoidosis recovered to normal sinus rhythm after corticosteroid therapy in 57% 2, 3. On the other hand, a systemic review demonstrated that corticosteroids might have little benefit on VT from cardiac sarcoidosis 4…”
Section: Introductionmentioning
confidence: 99%
“…Although preliminary in nature, the results show that patients with episodes of sustained VT had significantly higher FDG uptake when compared with Studies reporting correlations between abnormalities on imaging and clinical presentation in CS patients, particularly using FDG PET, are extremely limited, and quantitative analysis of SUV values has not previously been used for this purpose. Banba et al 17 performed Gallium scanning in 15 CS patients presenting with either AVB or VT. Interestingly, abnormal Gallium uptake was documented in 80% of AVB patients, but only 14% of the VT cohort. Similar to our results EF was lower and there was a high prevalence of perfusion abnormalities in the VT cohort.…”
Section: Discussionmentioning
confidence: 99%
“…3 In our series, 56% (18/32) of the total group and 69% (18/26) of the biopsy-diagnosed patients had an ICD implanted. It may be that arrhythmias respond poorly to immunosuppression in GCM because, as in cardiac sarcoidosis, 12 they are related to myocardial scars rather than to active inflammation.…”
mentioning
confidence: 99%